Wielowymiarowa analiza korespondencji jako narzędzie wspomagające segmentację międzynarodową bazującą na konsumpcyjnych łańcuchach celów i środków - Sobczak, Elżbieta (Multiple Correspondence Analysis as a Tool for International Segmentation, Based on Consumers Means-End Chains, 2008)
The objective of the paper becomes the proposal of multiple correspondence analysis (MCA) application for the purposes of international segmentation. The criteria for the segmentation are based on consumers' means-end-chains, i.e. ways for associating product attributes with advantages resulting from its usage, as well as values which are the consequences of such advantages. The application of MCA facilitated the graphical presentation of coexisting clusters of segmentation criteria and profile variables. The study also takes up an attempt of evaluating practical significance resulting from the applied multidimensional statistical analysis method.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 305-315